Surgical site infection and costs in low- and middle-income countries: A systematic review of the economic burden - Monahan, Mark; Jowett, Susan; Pinkney, Thomas; Brocklehurst, Peter; Morton, Dion G.; Abdali, Zainab; Roberts, Tracy E. (PloS one, 2020)
Surgical site infection (SSI) is a worldwide problem which has morbidity, mortality and financial consequences. The incidence rate of SSI is high in Low- and Middle-Income countries (LMICs) compared to high income countries, and the costly surgical complication can raise the potential risk of financial catastrophe. The aim of the study is to critically appraise studies on the cost of SSI in a range of LMIC studies and compare these estimates with a reference standard of high income European studies who have explored similar SSI costs. A systematic review was undertaken using searches of two electronic databases, EMBASE and MEDLINE In-Process & Other Non-Indexed Citations, up to February 2019. Study characteristics, comparator group, methods and results were extracted by using a standard template. Studies from 15 LMIC and 16 European countries were identified and reviewed in full. The additional cost of SSI range (presented in 2017 international dollars) was similar in the LMIC ($174-$29,610) and European countries ($21-$34,000). Huge study design heterogeneity was encountered across the two settings. SSIs were revealed to have a significant cost burden in both LMICs and High Income Countries in Europe. The magnitude of the costs depends on the SSI definition used, severity of SSI, patient population, choice of comparator, hospital setting, and cost items included. Differences in study design affected the comparability across studies. There is need for multicentre studies with standardized data collection methods to capture relevant costs and consequences of the infection across income settings.